Strengthening of bolted shear joint in ferrocement construction - Chiong, Chung Eng (2007)
This study deals with strengthening of bolted shear joint in thin-walled ferrocement construction. Such a joint is attractive because it provides faster and neat means of assembling precast elements into a complete structure. Steel wires, bent into O-Shape and U-shape with or without extra straight wire, are considered as simple inserts around the bolt hole to enhance the joint strength. The parameters investigated include the number of layers of wire mesh (or volume fraction of reinforcement), edge distance of bolt hole and the effectiveness of different types of the steel inserts. Test results have shown that for small edge distance, failure occurs either in cleavage or shearing mode, and the strength of the joint increases with an increase in the edge distance. This continues up to an upper limit set by either tension or bearing failure. For a given edge distance and details of connected members, the strength of a joint can be significantly enhanced by using steel insert, while U-insert is most cost-effective. Available equations for predicting the joint strength in ferrocement composites can be slightly modified to include the effects of these inserts with a good level of accuracy. Since the cleavage failure equation is quite conservative, removing it from consideration or modifying it to reflect test data can improve the accuracy of the predictions of joint strength. As an alternative, strut-and-tie model, herein can predict the joint strength in ferrocement composite as proposed. However it does not perform that well if steel insert is included in the ferrocement plate, as the process to determine volume fraction of reinforcement becomes more complex.